2000
DOI: 10.1897/1551-5028(2000)019<0793:mtvdoc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Vertical Distribution of Carbendazim in Sediments

Abstract: The sorption, fate, and vertical distribution of the fungicide Derosal with active ingredient carbendazim in sediments were investigated in indoor freshwater microcosms. Carbendazim penetration in the sediment was measured as a function of time and depth. Freundlich sorption parameters were determined by batchwise equilibration of carbendazim in a sediment suspension. Freundlich parameters were K f ϭ 258 g (1Ϫn) L n /kg and n ϭ 0.78. Analysis of different layers of sediment cores showed a slow penetration of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It has been shown that the application of AC without mixing is nearly as effective as application with initial brief mixing (Sun and Ghosh 2007;. A high effectiveness of the PAC treatment after only initial mixing in field scale bioaccumulation experiments has been observed (Kupryianchyk et al 2013b) indicating that subsequent mixing by bioturbation (Matisoff 1982;Koelmans and Jonker 2011;Kupryianchyk et al 2013a;Lin et al 2013), turbulent dispersion due to wind induced pressure gradients (Koelmans et al 2000), or direct wind-induced resuspension were able to ascertain sufficient mixing of AC. For bioturbation, it has been shown that the presence of bioturbators tolerant to AC addition, may on the one hand enhance mixing and facilitate HOC mass transport to AC particles, whereas on the other hand increase sediment-to-water fluxes of HOCs and thus reduce the effectiveness of AC in lowering overlying water concentrations Kupryianchyk et al 2013a;Lin et al 2013).…”
Section: Activated Carbon Applicationmentioning
confidence: 99%
“…It has been shown that the application of AC without mixing is nearly as effective as application with initial brief mixing (Sun and Ghosh 2007;. A high effectiveness of the PAC treatment after only initial mixing in field scale bioaccumulation experiments has been observed (Kupryianchyk et al 2013b) indicating that subsequent mixing by bioturbation (Matisoff 1982;Koelmans and Jonker 2011;Kupryianchyk et al 2013a;Lin et al 2013), turbulent dispersion due to wind induced pressure gradients (Koelmans et al 2000), or direct wind-induced resuspension were able to ascertain sufficient mixing of AC. For bioturbation, it has been shown that the presence of bioturbators tolerant to AC addition, may on the one hand enhance mixing and facilitate HOC mass transport to AC particles, whereas on the other hand increase sediment-to-water fluxes of HOCs and thus reduce the effectiveness of AC in lowering overlying water concentrations Kupryianchyk et al 2013a;Lin et al 2013).…”
Section: Activated Carbon Applicationmentioning
confidence: 99%
“…Therefore, the diffusion of Arochlor 1242 to a depth of less than 10 mm in 43 days is in good agreement with results showed here. Studies on the diffusion of carbendazim in sediment by Koelmans and co-workers (22) revealed a behavior similar to those of simazine and lindane, in agreement with their respective hydrophobicity. In the modeling of concentration profiles of carbendazim, Koelmans used organic matternormalized Freundlich coefficients to describe the sorption of the fungicide.…”
Section: Resultsmentioning
confidence: 72%
“…Applying this methodology to data from another Sharom and Solomon (11), for example, a Kd of 389 L kg -1 , revealed a depth of diffusion of only 1.8-2.0 mm as compared to the observed >10 mm observed diffusion. A comparison to less hydrophobic pesticides, lindane, simazine, and carbendazim, from other studies is also provided in Table 2 (15,22).…”
Section: Resultsmentioning
confidence: 99%
“…This means that we varied the parameters one by one by multiplying them with a factor of either 1.1 or 0.9, while all the other parameters remain constant. This method has shown its feasibility and reliability and has been extensively applied in contaminant fate modeling (Koelmans et al 2000. The model usually responded linearly to the small variation applied to the parameters (10%), thus does not affect the model but only reveals the importance of these parameters (Saltelli et al 2000).…”
Section: Model Sensitivity and Uncertainty Analysismentioning
confidence: 99%